Pilkada dan pemekaran daerah dalam demokrasi lokal Indonesia: local strongmen dan roving bandits - LEO Agustino,; Mohammad Agus Yusoff, (Penerbit UKM, 2010)
This article discusses the process of democratization at the local level in Indonesia by looking at the mechanism of electing heads of local district (Pilkada) and the creation of new districts. Pilkada is seen as the best solution to cultivate local democracy in Indonesia after the collapse of the New Order. During Soeharto rule, democracy at the local level was seen as ‘dead', especially with the emergence of local strongmen and central political elites (stationary bandits). During that time, local leaders were merely seen as tools to take care Jakarta's interest instead of that of the local people. However, after the downfall of the Soeharto regime, people's hopes for changes through Pilkada and the creation of new district failed to materialize. This is due to continuous strong role played by local strongmen who used stationary bandits to block political transformations from taking place. This article, therefore, discusses the role played local strongmen and stationary bandits in both during the Soeharto and Reformasi period. The main focus of this article is to analyze how the interaction between local strongmen and the stationary bandits during the New Order and the Reformasi era contributed to the creation of new districts, and to discuss the strategy of those roving bandits in dominating and exploiting the district politics. The main argument of this article is that local strongmen and roving bandits are still controlling local politics, though Indonesia has undergone political for almost a decade. Local democracy is still dictated by the interest of local elites.